Iron(II), Cobalt(II), and Nickel(II) Complexes of Bis(sulfonamido)benzenes: Redox Properties, Large Zero-Field Splittings, and Single-Ion Magnets - Bamberger, Heiko; Albold, Uta; Dubnická Midlíková, Jana; Su, Cheng-Yong; Deibel, Naina; Hunger, David; Hallmen, Philipp P; Neugebauer, Petr; Beerhues, Julia; Demeshko, Serhiy; Meyer, Franc; Sarkar, Biprajit; et al. (Inorganic chemistry, 2021)
Metal complexes of 1,2-diamidobenzenes have been long studied because of their intriguing redox properties and electronic structures. We present here a series of such complexes with 1,2-bis(sulfonamido)benzene ligands to probe the utility of these ligands for generating a large zero-field splitting (ZFS, ) in metal complexes that possibly act as single-ion magnets. To this end, we have synthesized a series of homoleptic ate complexes of the form (X) [M{bis(sulfonamido)benzene} ] ( equals 4 minus the oxidation state of the metal), where M (Fe/Co/Ni), X [K /(K-18-c-6) /(HNEt ) , with 18-c-6 = 18-crown ether 6], and the substituents (methyl and tolyl) on the ligand [bmsab = 1,2-bis(methanesulfonamido)benzene; btsab = 1,2-bis(toluenesulfonamido)benzene] were varied to analyze their effect on the ZFS, possible single-ion-magnet properties, and redox behavior of these metal complexes. A combination of X-ray crystallography, (spectro)electrochemistry, superconducting quantum interference device magnetometry, high-frequency electron paramagnetic resonance spectroscopy, and Mössbauer spectroscopy was used to investigate the electronic/geometric structures of these complexes and the aforementioned properties. These investigations show that the cobalt(II) complexes display very high negative values in the range of -100 to -130 cm , and the nickel(II) complexes display very high positive values of 76 and 58 cm . In addition, the cobalt(II) complexes shows barriers of 200-260 cm and slow relaxation of the magnetization in the absence of an external magnetic field, underscoring the robustness of this class of complexes. The iron(II) complex exhibits a value of -3.29 cm and can be chemically oxidized to an iron(III) complex that has = -1.96 cm . These findings clearly show that bis(sulfonamido)benzenes are ideally suited to stabilize ate complexes, to generate very high ZFSs at the metal centers with single-ion-magnet properties, and to induce exclusive oxidation at the metal center (for iron) despite the presence of ligands that are potentially noninnocent. Our results therefore substantially enhance the scope for this class of redox-active ligands.